2020
DOI: 10.3892/mmr.2020.11447
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑22 regulates autophagy and apoptosis in cisplatin resistance of osteosarcoma

Abstract: osteosarcoma (oS) is a primary malignant tumor of bone tissue. effective chemotherapy may improve the survival of patients with OS. MicroRNAs (miRs) serve significant roles in the regulatory function of tumorigenesis and chemosensitivity of different types of cancer. mir-22 has been revealed to inhibit the proliferation and migration of oS cells, as well as increasing their sensitivity to cisplatin (cddP). The mechanisms of action behind the functions of mir-22 in oS drug resistance require investigation. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…CDDP combined with advanced surgery is widely used for the treatment of OS, but as drug resistance increases, the prognosis of patients becomes more unfavourable. Numerous noncoding RNAs, such as circRNAs and miRNAs, have been shown to be involved in the development of drug resistance in OS [ 53 , 54 ]. According to in vitro and in vivo studies, overexpression of circPRKAR1B suppressed the resistance of OS cells to CDDP.…”
Section: Discussionmentioning
confidence: 99%
“…CDDP combined with advanced surgery is widely used for the treatment of OS, but as drug resistance increases, the prognosis of patients becomes more unfavourable. Numerous noncoding RNAs, such as circRNAs and miRNAs, have been shown to be involved in the development of drug resistance in OS [ 53 , 54 ]. According to in vitro and in vivo studies, overexpression of circPRKAR1B suppressed the resistance of OS cells to CDDP.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 43 investigated the molecular regulatory mechanisms of lncRNAs in chemotherapeutic drug resistance in OS, 101 focused on miRNAs, 21 on circRNAs, and one study reported on both lncRNA MEG3 and hsa_circ_0001258 ( Zhu et al, 2019 ). Moreover, 19 overlapping ncRNAs were reported in more than one study, including four lncRNAs (lncRNA SNHG15 [ Sun et al, 2022 ; Zhang et al, 2020a ], lncRNA OIP5-AS1 [ Song et al, 2019 ; Liu and Wang, 2020 ; Sun et al, 2020 ; Kun-Peng et al, 2019 ], lncRNA TUG1 [ Zhou et al, 2020 ; Hu et al, 2019 ], and lncRNA ANRIL [ Li and Zhu, 2019b ; Lee et al, 2021 ]), 13 miRNAs (miR-29b [ Luo et al, 2019 ; Li et al, 2020 ], miR-21 [ Vanas et al, 2016 ; Ziyan and Yang, 2016 ], miR-22 [ Wang et al, 2019c ; Li et al, 2014 ; Meng et al, 2020a ; Meng et al, 2020b ; Zhou et al, 2018b ], miR-199a-3p [ Lei et al, 2018 ; Gao et al, 2015 ], miR-34a-5p [ Pu et al, 2016 ; Pu et al, 2017b ; Pu et al, 2017a ], miR-34a [ Li et al, 2017 ; Novello et al, 2014 ; Chen et al, 2016a ], miR-140-5p [ Wei et al, 2016 ; Meng et al, 2017 ], miR-203 [ Chen et al, 2016a ; Huang et al, 2021 ], miR-19a-3p [ Zhang et al, 2019 ; Wang et al, 2022a ], miR-140 [ Song et al, 2009 ; Zhi et al, 2022 ], miR-29 [ Osaki et al, 2016 ; Xu et al, 2018b ], miR-221 [ Yu et al, 2019 ; Zhao et al, 2013 ], and miR-100 [ Xiao et al, 2017 ; Liu et al, 2016 ]), and two circRNAs (circPTV1 [ Li et al, 2021c ; Kun-Peng et al, 2018a ; Wang et al, 2022c ] and circRNA_0004674 [ Ma et al, 2021 ; Bai et al, 2021 ]) (…”
Section: Resultsmentioning
confidence: 99%
“…It has been well documented that autophagy exerts key roles in increasing CDDP resistance in OS cells [ 34 ]. By contrary, inhibited autophagy is capable of boosting sensitivity of OS cells to CDDP, along with the reduced Beclin1 level and LC3-II/LC3-I ratio [ 35 , 36 ]. In recent years, studies have found that lncRNA-mediated dysregulation of targets and pathways is considered to be the key cause of chemotherapy resistance [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%